Pendampingan Pendaftaran NIB dan Pelatihan Media Sosial guna Meningkatkan Ekonomi UMKM di Kelurahan Bulak - Yanuar Tyas Suganda; Sri Muljaningsih; Mohammad Wahed (IAIN AMBON, 2022)
The KKNT activities for Defending the State UPN Veteran East Java are a challenge for students who are still experiencing restrictions on movement due to the Covid-19 pandemic in 2022. One of the areas targeted by the MBKM KKNT in 2022 is Bulak with an entrepreneurial and creative economy scheme. From the results of surveys and field observations, it was found that partner problems such as the way of selling products that were felt to be still monotonous, product designs that were less valued and the scope of marketing was still not wide, as well as several UMKM that did not have business legality, namely NIB. Therefore, the KKN student team from UPN formulated a work program that is expected to solve existing problems. The target audience in this case is that UMKM owners can increase their potential through various UMKM development strategies. The results of the socialization activities & training of various materials in general went according to plan. The potential resulting from this service activity is that UMKM in Bulak can compete, especially diversifying the local market and even exporting with digitalized and structured marketing methods with the use of social media and emphasizing product value branding.